PENERAPAN LITERASI KEUANGAN SYARIAH PADA SEKOLAH AN-NIKMAH PHNOM PENH, KAMBOJA - Muhammad Mahardhiko; Rahmayati (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the implementation of Islamic financial literacy at An-Nikmah School in Phnom Penh, Cambodia. The research method used is a qualitative descriptive method with data collection techniques through observation, interviews, and documentation of students representing 30 people divided between grades 8 and 9. The results of the study indicate that Islamic financial literacy in this school is still low due to the lack of education and the lack of teaching materials available in a language that is easy for students to understand. To overcome this, various strategies are carried out such as the integration of Islamic financial literacy into the curriculum, sharia transaction simulations, and wider socialization to students and educators. The conclusion of this study found that there is a great opportunity to improve Islamic financial literacy by utilizing digital technology and support from the local Muslim community. Increasing Islamic financial literacy is expected to help students understand and apply the principles of Islamic finance in everyday life. Keywords : Islamic financial literacy, financial education, improvement